The Application of the Lex Loci Celebrationis Principle in the Execution of Notarial Deeds Involving Foreign Legal Subjects - Thea Farina (International Journal of Law and Society, 2026)
This article provides a comprehensive examination of the application of the lex loci celebrationis principle in the execution of notarial deeds involving foreign legal subjects within the Indonesian legal system. The principle affirms that any authentic deed executed in Indonesia must comply with national legal requirements, regardless of the parties’ nationality or the existence of transnational legal relations. Through normative legal research employing statutory, conceptual, comparative, and case-study approaches, this article elucidates how the lex loci celebrationis principle interacts with private international law, particularly in relation to the legal capacity of foreign nationals, the use of foreign documents, and the limits of jurisdiction. The analysis reviews the Law on Notarial Office, the Indonesian Civil Code, population administration regulations, as well as doctrinal developments and jurisprudence pertaining to international legal acts. The findings indicate that although the substantive aspects of an agreement may refer to foreign law through lex voluntatis, the formal validity of a notarial deed remains entirely governed by Indonesian law. These findings underscore the need to enhance the competence of notaries in understanding the dynamics of private international law and highlight the importance of harmonizing national regulations with the principles of private international law to ensure legal certainty in cross-border transactions.